PENINGKATAN KEMAMPUAN MELAKSANAKAN PEMBELAJARAN YANG BERBASIS SAINTIFIK MELALUI REKTIFIKASI HASIL SUPERVISI PEMBELAJARAN GURU MATEMATIKA DAN IPA BAGI ASN DI SMA NEGERI 3 BARRU PROVINSI SULAWESI SELATAN - Mustamin Mustamin (Jurnal Kewidyaiswaraan, 2021)
Improving the Ability to Implement Scientific-Based Learning Through the Results Supervision Rectification of Learning Mathematics and Science Teachers at SMA Negeri 3 Barru”. This study aims to find out how much the ability to carry out scientific-based learning through the result rectification learning supervision of mathematics and science teachers of SMA Negeri 3 Barru. The type of research used is school action research (School Action Researt). The population of this study were all mathematics and science teachers at SMA Negeri 3 Barru consisting of 5 mathematics teachers, 2 biology teachers, 2 physics teachers and 2 chemistry teachers. The sample was the mathematics and science teacher at SMA Negeri 3 Barru as a saturated sample consisting of 4 boys and 5 girls. This research was conducted in the even semester of the 2019/2020 academic year. This research was conducted in 6 meetings. Data were collected by using observation sheets with learning supervision observation instruments ranging from pre-observation, observational observation of learning implementation to the implementation of feedback for each teacher after being supervised. The data were analyzed using qualitative and quantitative descriptive analysis. The results of the research as a whole show that: (1) There is an increase in the ability of mathematics and science teachers in carrying out scientific-based learning as evidenced by the results of supervising learning through pre-observation, namely the preparation of teaching and learning activities, there is an increase based on the results of initial observations there is an average score (76.06% ) in the good category, in the first cycle there was an increase in the average score (82.61%) in the good category, in the second cycle there was an increase (88.17%) in the very good category. Based on these results, the authors concluded that after the supervision activities rectification results of Learning Supervision can provide a significant contribution to the improvement of the ability to carry out learning based on scientific mathematics teachers SMA and Negeri 3 Barru..